HARMONIZED COGNITIVE ASSESSMENT FOR LARGE POPULATION STUDIES. (11th November 2018) - Weir, D; Ryan, L; Langa, K M
Abstract: We describe the development and implementation of the Harmonized Cognitive Assessment Protocol, which was created for the assessment of dementia and mild cognitive impairment in the US Health and Retirement Study and it sister studies around the globe. It is based on best-practice instruments for multiple cognitive domains and informant reports, and designed for flexible statistical harmonization with other US studies, including the HRS-ADAMS study, the Rush Memory and Aging Project, and the Alzheimer's Disease Neuro-Imaging Initiative, and also with other international studies including the 10/66 project. It has been used successfully in the US, England, Mexico, China, India, and South Africa.